Parent-identified barriers to accessing exposure therapy: A qualitative study using process mapping - Frank, Hannah E.; Cain, Grace; Freeman, Jennifer; Benito, Kristen G.; O’Connor, Erin; Kemp, Josh; Kim, Bo (Frontiers in Psychiatry, 2023)
Background: Youth with anxiety and obsessive-compulsive disorder (OCD) rarely access exposure therapy, an evidence-based treatment. Known barriers include transportation, waitlists, and provider availability. Efforts to improve access to exposure require an understanding of the process that families take to find therapists, yet no prior studies have examined parents’ perspectives of the steps involved. Methods: Parents of children who have received exposure therapy for anxiety and/or OCD (N=23) were recruited from a hospital-based specialty anxiety clinic where the majority of their children previously received exposure. Recruitment was ongoing until thematic saturation was reached. Parents completed questionnaires and attended an online focus group during which they were asked to describe each step they took - from recognizing their child needed treatment to beginning exposure. A process map was created and shown in real-time, edited for clarity, and emailed to parents for member checking. Authors analyzed process maps to identify common themes. Results: Several themes emerged, as visually represented in a final process map. Participants identified a “search-outreach” loop, in which they repeated the cycle of looking for therapists, contacting them, and being unable to schedule an appointment due to factors such as cost, waitlists, and travel time. Parents often did not know about exposure and reported feeling guilty about their lack of knowledge and inability to find a suitable provider. Parents reported frustration that medical providers did not often know about exposure and sometimes dismissed parents’ concerns. Participants emphasized the difficulty of navigating the mental health system; many reported that it took years to find an exposure therapist, and that the search was sometimes stalled due to fluctuating symptoms. Conclusions: A common thread among identified barriers was the amount of burden placed on parents to find treatment with limited support, and the resultant feelings of isolation and guilt. Findings point to several directions for future research, such as the development of parent support groups for navigating the mental health system; enhancing coordination of care between medical and mental health providers; and streamlining referral processes.